Examining Biases in ABS-CBN Online News: A Framing Analysis of Reporting about President Ferdinand Marcos Jr. - Robiego, Jeanard Anthony M.; Talde, Danna Karyl Jane C. (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
ABS-CBN, a leading media entity in the Philippines, has often found itself embroiled in controversies surrounding accusations of bias, particularly in its coverage of President Ferdinand